2005
DOI: 10.1021/jp054036v
|View full text |Cite
|
Sign up to set email alerts
|

MX3- Superhalogens (M = Be, Mg, Ca; X = Cl, Br):  A Photoelectron Spectroscopic and ab Initio Theoretical Study

Abstract: Gas-phase alkaline earth halide anions, MgX3(-) and CaX3(-) (X = Cl, Br), were produced using electrospray and investigated using photoelectron spectroscopy at 157 nm. Extremely high electron binding energies were observed for all species and their first vertical detachment energies were measured as 6.60 +/- 0.04 eV for MgCl3(-), 6.00 +/- 0.04 eV for MgBr3(-), 6.62 +/- 0.04 eV for CaCl3(-), and 6.10 +/- 0.04 eV for CaBr3(-). The high electron binding energies indicate these are very stable anions and they belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
116
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(121 citation statements)
references
References 97 publications
4
116
0
1
Order By: Relevance
“…6 Owing to this character, superhalogens have wide application potentials in the fields of synthesis, 3,5,7,8 new dopants to improve the electrical conductivity of polymers 1,3 and production of new materials. [2][3][4][5]7,9 Gutsev and Boldyrev, who first introduced the term "superhalogen" in early 1980s, 1 have proposed a simple formula MX k+1 for traditional superhalogens, 1,2,10 where M is the central atom, k is the maximal formal valence of atom M, and X is halogen atom as ligand.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Owing to this character, superhalogens have wide application potentials in the fields of synthesis, 3,5,7,8 new dopants to improve the electrical conductivity of polymers 1,3 and production of new materials. [2][3][4][5]7,9 Gutsev and Boldyrev, who first introduced the term "superhalogen" in early 1980s, 1 have proposed a simple formula MX k+1 for traditional superhalogens, 1,2,10 where M is the central atom, k is the maximal formal valence of atom M, and X is halogen atom as ligand.…”
Section: Introductionmentioning
confidence: 99%
“…5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Along with the deepening of the related researches, it has been a Author to whom correspondence should be addressed. Electronic mail: rayinyin@nwu.edu.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very first experimental evidence of the superhalogen existence was provided in 1999 by the Wang's group who reported the photoelectron spectra of the selected triatomic MX 2 − superhalogen anions (M = Li, Na; X = Cl, Br, I) [8]. Since then, many other superhalogen anions [e.g., Na k Cl − k+1 (k = 1-4) and MX 3 − (where M = Be, Mg, Ca; X = Cl, Br)] have also been identified experimentally [9,10]. As indicated by both theoretical predictions and experimental measurements, the original superhalogen formula (MX k+1 ) can be extended to include the polynuclear M n X nk+1 neutral superhalogen compounds (containing n central atoms) whose corresponding polynuclear M n X − nk+1 anions exhibit even larger electron binding energies than their mononuclear counterparts [11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…Subsequently, several experimental studies have confirmed the existence of superhalogens consisting of simple metal atoms, such as alkalis, Mg, and Al at the core and halogen atoms on the periphery. [5][6][7] Considerable research conducted in recent years has shown that superhalogens not only mimic the chemistry of halogens but also can be used to promote unusual reactions, 8 as a building block of energetic materials, 9 as dopants to increase the electrical conductivity of polymers, 10 for accessing high oxidation states of metal atoms, 11 as electrolytes in rechargeable batteries, 12 and in the production of organic superconductors and organic metals. 13 What has not been addressed in the literature is the electron affinity of species created by combing two or more superhalogens.…”
mentioning
confidence: 99%